Literature Review: Effectiveness of Early Mobilization on Clinical Outcomes of Mechanically Ventilated Patients in the Intensive Care Unit - Efikal Efikal; Sri Wahyuni; Dwi Retno Sulistyaningsih; Suyanto Suyanto (Indonesian Journal of Global Health Research, 2025)
Early mobilization of mechanically ventilated patients in the intensive care unit is an important intervention in preventing immobilization complications such as muscle weakness, decreased functional capacity, and prolonged length of stay. Despite its widely reported benefits, the implementation of early mobilization still faces various challenges, including limited resources, risk perception, and lack of systematic guidelines. Objectives: This study aimed to evaluate the effectiveness of early mobilization on clinical outcomes of mechanically ventilated patients in the intensive care unit through a literature review. Methods: This study used a systematic literature review approach by searching national and international scientific articles published in the last five years, 2020-2025. The search was conducted through three main databases: PubMed, Google Scholar, and SciSpace. The search strategy referred to the PICO (Population, Intervention, Comparison, Outcome) framework using keywords such as “early mobilization”, “mechanical ventilation”, “ICU outcomes”, and “clinical outcomes”. From a total of 108 articles found, an initial screening process eliminated duplicates and irrelevant articles, resulting in 32 articles for further review. After a selection process based on inclusion and exclusion criteria, only 9 articles met all criteria and were analyzed in depth. Results: The review showed that early mobilization positively contributed to various clinical outcomes, including increased muscle strength, reduced duration of ventilator use, decreased length of stay, and improved functional status of post-ICU patients. The success of this intervention was influenced by the involvement of a multidisciplinary team, clear mobilization protocols, and adequate training for health workers.